Urban road network safety model at the transportation planning process - Sara Ferreira (2013)
The transportation planning process is considered to be the initial step to incorporate the safety analyses of a transport system. Recently, tools have been created for this incorporation, although the vast majority has been applied at an area level. Despite the capacity of these tools to provide safety information, they are unable to identify hazardous locales in the network. The primary objective of this article was to develop a tool based on accident prediction models, which enable the forecasting of the highest accident-risk entities (i.e., nodes or links) using the information available as well as meeting the main issues that are decided at the planning level. Analyzing the influence of macrolevel road design variables on accident risk was the second objective, providing knowledge for planners and decision makers. To accomplish these objectives, generalized linear modeling techniques were employed to develop models for nodes and links using data from Porto, Portugal. The result analysis demonstrates that the additional macrolevel variables are statistically significant and improves the model. Thus, the results lead to a general conclusion that the proposed models are the suitable tool because they embody the balance between the needs and constraints inherent to the planning level. Â© 2013 Copyright Taylor and Francis Group, LLC.